Co-generation of acetone-butanol-ethanol and lipids by a sequential fermentation using Clostridia acetobutylicum and Rhodotorula glutinis, spaced-out by an ex-situ pervaporation step. (20th February 2021) - Zhang, Changwei; Si, Zhihao; Chen, Bo; Chen, Changjing; Chen, Huidong; Ren, Wenqiang; Cheng, Shikun; Li, Shufeng; Cai, Di; Qin, Peiyong
Abstract: Large amounts of effluent discharge and a costly wastewater treatment hinder the scale-up of the lignocellulosic acetone-butanol-ethanol (ABE) fermentation process. By recycling the broth after solvents removal and using it in the subsequent cycles of biomass hydrolysis and fermentation, the overall amount of effluent can be reduced. However, the ABE production is severely inhibited by the accumulated acids and other toxic by-products when reusing the cycled streams. In this study, a pervaporation assisted sequential fermentation was performed. The ABE liquor recovered after batch fermentation and ex situ pervaporation was used as the buffer for corn stover pulp hydrolysis and the following microbial lipids fermentation. In microbial lipids fermentation stage, toxic acid by-products remained in the liquor can be co-utilized as a substrate. The acids eliminated post-harvested broth was further cycled as the buffer for pulp hydrolysis and ABE fermentation. As a result, ABE yield of 0.349 g/g and concentration of 14.40 g/L were achieved after 3 cycles of operation, which show only 3.86% and 14.98% reduction compared to those of the initial cycle. Remarkably, the effluent discharge was reduced by 92.20% after applying the hybrid two-stage sequential fermentation. Meanwhile, 8.20 g/L of microbial lipids can be co-generated. The novel process offers an environmentally friendly strategy for the co-production of ABE and microbial lipids from lignocelluloses under the concept of biorefinery. Graphical abstract: Image 1 Highlights: ABE fermentation was hybrid with ex situ pervaporation and microbial lipids fermentation. The effluent wastewater in the hybrid process was reused by a recycled loop. Acids by-product in the ABE fermentation broth can be used as carbon source for lipids production. Total 3 cycles of was conducted with 92.20% of ABE wastewater saving rate. ABE and lipids production were not obvious decreased within 3 cycles of operation.